Stres Kerja Pada Perawat di Ruang Perawatan Pediatrik - Satmayani Satmayani; Syahrul Syahrul; Ariyanti Saleh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Background: Stress is one of the problems in the nursing profession. The incidence of stress in nurses is quite high due to various factors. Pediatric nursing is a specialization unit that focuses on stress. Stress on nurses in addition to health, also affects freedom to stop work and turnover, patient care becomes ineffective, indifference to patients and colleagues and medical errors. The purpose of this literature is to discuss stress, stressors, and stress that can be used to treat stress. Methods: search for scientific articles using a database including, Pubmed, Google Scholar, Science Direct and searches in 2009-2018 with keywords